Función cuadrática: espacio de trabajo matemático idoneo de profesores en ejercicio - Pinto Lazares, Miriam Roxana (2024)
The purpose of this study is to investigate how a high school mathematics teacher in Basic Regular Education approaches the analysis, specifically when presenting lessons on quadratic functions to fourth-year high school students. An essential element of this analysis involves examining how the teacher organizes the content and proposed activities during the instruction of the quadratic function. This is supported by the use of the Ministry of Education's book, "Mathematics Worksheet 4th Year," and the use of GeoGebra software, taking into account the problems noted in previous research related to learning in this area. Additionally, documents such as the National Curriculum Design (DCN) emphasize the importance of convering the quadratic function. The difficulty we have discovered leads us to define the main objective of this research, which is to analyze the ideal mathematical environment of the high school teacher when teaching lessons on the quadratic function to fourth-year students. To achieve this goal, we rely on the theory of the Mathematical Work Space (MWS) proposed by Kuzniak. Regarding the methodology, we have opted for a qualitative approach, following the steps defined by Hernández, Fernández, and Baptista, which have been adapted to fit the nature and specific objectives of this study. The research is conducted through the observation of a learning session, complemented by interviews. This data allows us to exhibit and examine the actions of the high school teacher when teaching the quadratic function, identifying the activated genesis and planes, as well as the analysis paradigms prioritized. The results reveal that, during the learning session, the teacher activates semiotic, instrumental, and discursive genesis, as well as the semioticinstrumental, instrumental-discursive, and semiotic-discursive planes. Additionally, the teacher's preference for working within the paradigms of Geometric/Arithmetic Analysis and Calculator Analysis is highlighted.